Analisis Penggunaan system Informasi pada Bisnis Online sabun Nyrtea - Jelita Handayani Rambe; Muhammad Aziz Alfarisi; Winda Irmayani Sijabat; Nurbaiti Nurbaiti (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
This study aims to determine the use of an information system applied to the online sale of Nyrtera soap. This research uses a qualitative method that contains explanations about the object under study based on primary data obtained through the results of interviews and literature studies. The nature of this study is descriptive analytical. The research location is in the Medan branch, North Sumatra. Based on the results of the study, it can be concluded that the use of the information system used in Nyrtea Soap e-commerce is a social media and online sales platform, namely through the Shopee application and through orders on social media which will later be connected via the WhatsApp Business chat listed. Sales on social media and shopee are paid for through digital and traditional payments that use courier services in delivering goods and use microsoft office excel in data collection. Keywords: Information System, Online Business, Nyrtea Soap